Cardiac Rehabilitation practitioners’ views on patients’ psychological needs: a qualitative study - Wray, Laura; Capobianco, Lora; Wells, Adrian (Frontiers in Psychiatry, 2024)
Background Psychological difficulties are prevalent in patients who attend Cardiac Rehabilitation (CR). Recent guidelines recommend practitioners enquire and support patients' psychological concerns within CR. Therefore, Study One aimed to explore practitioners' understanding of patients' psychological needs, their confidence in supporting those needs and views on whether current CR meets patients' needs.Study Two aimed to validate Study Ones' findings among a wider sample of CR practitioners.One utilised qualitative interview data from the PATHWAY trial (REC Reference:15/NW/0163), while Study Two utilised new interview data collected as part of the PATHWAY Beacons study (REC reference: 22/HRA/2220). In Study One semi-structured interviews with six CR practitioners were analysed using thematic analysis. In Study Two, 11 CR practitioners across England were interviewed using member checking principles. Transcripts were coded systematically using the codes developed from Study One and, through constant comparative analysis.Results: Four main themes were identified: staff's awareness of mental health problems faced, CR patients' needs, staff's self-efficacy to support patients' psychological needs, and current psychological provision in CR. The main themes, and 11 subthemes were transferable to a wider range of CR practitioners, indicating trustworthiness of the findings.Practitioners described patients experience a range of psychological concerns, including adjustment difficulties, anxiety, cardiac and non-cardiac worries.Most practitioners normalise patients' concerns and offer relaxation techniques. However, practitioners noted patients often have complex psychological needs, but practitioners' confidence in discussing and supporting psychological concerns varies.Practitioners expressed a need to be trained to support patients' psychological needs.